2000
DOI: 10.1179/joc.2000.12.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Toxicity of Cisplatin in Bone Marrow Cells of Swiss Mice

Abstract: The inorganic platinum compound cisplatin (CP) in Oncoplatin, an anticancer drug, as the test chemical and cyclophosphamide (CY) in Endoxan, another anticancer drug, as the positive control, were tested for their cytogenetic toxicity in bone marrow cells of Swiss mice. The end points selected were mitotic metaphase chromosomal aberration and mitotic index study at 24-hour post-treatment and micronucleus test at 30-hour post-treatment after a single intraperitoneal exposure. The doses of the chemicals tested we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…In chromosomal aberration measurements, chromatid and isochromatid breaks were present more frequently, however gaps and complex exchanges were also observed. This evidence was supported by the previous studies, in which rat and mouse bone marrow cells were used (Edelweiss et al, 1995;Choudhury et al, 2000;Sendao et al, 2006). Gulkac et al (2004) have found that antineoplastic, doxorubicin produced an increased frequency of cells with chromosomal aberrations.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In chromosomal aberration measurements, chromatid and isochromatid breaks were present more frequently, however gaps and complex exchanges were also observed. This evidence was supported by the previous studies, in which rat and mouse bone marrow cells were used (Edelweiss et al, 1995;Choudhury et al, 2000;Sendao et al, 2006). Gulkac et al (2004) have found that antineoplastic, doxorubicin produced an increased frequency of cells with chromosomal aberrations.…”
Section: Discussionsupporting
confidence: 76%
“…It has been reported that cisplatin has a prominent clastogenity effect on the bone marrow cells from Wistar rats (Edelweiss et al, 1995). In a previous study, Choudhury et al (2000) found that single dose of cisplatin (5 mg/kg) led to an increase in the number of mitotic metaphase chromosomal aberrations and they have also concluded that the mitotic index did not change at 24 hours, which suggests that it is non-mitotoxic at given dose. Likewise, Mora et al (2002) have reported that single dose of cisplatin produced an increased frequency of cells with chromosomal aberrations and abnormal metaphases observed at 24th hour.…”
Section: Discussionmentioning
confidence: 95%
“…Antitumor platinum drugs induced intra-and interstrand cross-linking effects, chromosomal aberrations, SCE, and increased MN frequencies in a number of experimental systems in vitro and in vivo as well as in human cells [13,[31][32][33][34][35][36]. In addition, the activation of apoptotic cell death was described as a key defense mechanism by cisplatin to remove cells with severe DNA damage [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have clearly shown the deleterious effect of cytotoxic chemotherapy on protein synthesis and DNA replication resulting in diminished bone formation, but the precise mechanism has not been studied yet. 3 Therefore, in this study, we evaluated the effect of cisplatin on the survival of osteoblasts and applied the proteomics technology for identifying protein(s) involved in the action of cisplatin in osteoblasts.…”
mentioning
confidence: 99%